2018
DOI: 10.1038/eye.2017.306
|View full text |Cite
|
Sign up to set email alerts
|

Bruch’s membrane opening-based optical coherence tomography of the optic nerve head: a useful diagnostic tool to detect glaucoma in macrodiscs

Abstract: PurposeTo compare Bruch's membrane opening (BMO)-based spectral domain optical coherence tomography (SD-OCT) and margin based confocal scanning laser tomography (CSLT) of the optic nerve head (ONH) to visual field function in large optic discs (macrodiscs) and to assess performance for glaucoma detection.MethodsIn a case-control, cross-sectional study, 125 eyes of 125 patients with disc size >2.45 mm, thereof 44 glaucoma and 11 ocular hypertension (OHT) patients and 70 healthy controls underwent SD-OCT and CSL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 30 publications
1
28
0
2
Order By: Relevance
“…Previous studies have shown the clinical utility of BMO-MRW parameters in diagnosing glaucoma, especially in cases of extreme optic-disc sample size, demonstrating better diagnostic capability than confocal scanning laser tomography and exhibiting a good structure function correlation [9,21]. In general, many studies have shown the SD-OCT BMO-MRW and pRNFL thickness parameters to surpass confocal scanning laser tomography as regards diagnostic capacity to detect glaucoma [3,5,18,20,22].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the clinical utility of BMO-MRW parameters in diagnosing glaucoma, especially in cases of extreme optic-disc sample size, demonstrating better diagnostic capability than confocal scanning laser tomography and exhibiting a good structure function correlation [9,21]. In general, many studies have shown the SD-OCT BMO-MRW and pRNFL thickness parameters to surpass confocal scanning laser tomography as regards diagnostic capacity to detect glaucoma [3,5,18,20,22].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that the structure-function relationship is better with the BMO-MRW parameter than other conventional OCT-based and CSLO-based parameters [15,35,36]. Pollet-Villard et al [15] have demonstrated that the structure-function relationship is significantly greater with BMO-MRW than other optic disc OCT parameters including neuro-retinal rim thickness.…”
Section: Discussionmentioning
confidence: 99%
“…It is also stronger than RNFL thickness. Enders et al [35] have concluded that BMO-MRW seems to indicate the structure-function relationship better than RNFL thickness and rim area in CSLO. Recently, the structure-function relationship in lamina cribrosa (LC)-derived parameters has been inspected.…”
Section: Discussionmentioning
confidence: 99%
“…It has been lately shown that BMO-MRW provides better performance in the diagnosis of glaucoma than traditional NRR parameters [ 8 , 9 , 10 ]. BMO-MRW also shows a better structure-function relationship in glaucoma than other pre-existing peripapillary RNFL and parameters of confocal scanning laser ophthalmoscope [ 10 , 11 , 12 , 13 ]. We have previously described a disagreement between BMO-MRW and RNFL in classification analysis of color-codes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%